Enrichment of novel Verrucomicrobia, Bacteroidetes, and Krumholzibacteria in an oxygen‐limited methane‐ and iron‐fed bioreactor inoculated with Bothnian Sea sediments. Issue 1 (27th February 2021) - Dalcin Martins, Paula; de Jong, Anniek; Lenstra, Wytze K.; van Helmond, Niels A. G. M.; Slomp, Caroline P.; Jetten, Mike S. M.; Welte, Cornelia U.; Rasigraf, Olivia
Abstract: Microbial methane oxidation is a major biofilter preventing larger emissions of this powerful greenhouse gas from marine coastal areas into the atmosphere. In these zones, various electron acceptors such as sulfate, metal oxides, nitrate, or oxygen can be used. However, the key microbial players and mechanisms of methane oxidation are poorly understood. In this study, we inoculated a bioreactor with methane‐ and iron‐rich sediments from the Bothnian Sea to investigate microbial methane and iron cycling under low oxygen concentrations. Using metagenomics, we investigated shifts in microbial community composition after approximately 2.5 years of bioreactor operation. Marker genes for methane and iron cycling, as well as respiratory and fermentative metabolism, were identified and used to infer putative microbial metabolism. Metagenome‐assembled genomes representing novel Verrucomicrobia, Bacteroidetes, and Krumholzibacteria were recovered and revealed a potential for methane oxidation, organic matter degradation, and iron cycling, respectively. This work brings new hypotheses on the identity and metabolic versatility of microorganisms that may be members of such functional guilds in coastal marine sediments and highlights that microorganisms potentially composing the methane biofilter in these sediments may be more diverse than previously appreciated. Abstract : We identified novel bacteria potentially involved in methane and iron cycling in an oxygen‐limited bioreactor inoculated with methane‐ and iron‐rich Bothnian Sea sediments. Metagenomic analyses provided hypotheses about the mechanisms they may employ, such as the use of oxygen at very low concentrations. Our results imply that in more shallow sediments, where oxygen‐limited conditions are present, microorganisms potentially composing the methane biofilter may be more diverse than previously thought.